FST437: Basic Food Science & Technology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This is an introductory course in food science and technology. It covers an introduction to the food processing industry, food constituents, composition and processing of different food commodities, sensory and nutritional aspects, food safety and legislation.